MIMO digital beamforming for radar applications - Xing, Shan (2015)
Long range surveillance is a very demanding application for radar designers, and now generally requires active antennas with multiple transmitters for improved power budget, increased availability, and beams agility and adaptively. To satisfy these requirements, modern radars usually implement multiple channels and relatively wideband transmitting or receiving radio frequency front ends. This final year project report documents the design and implementation of space-time coding for a MIMO radar system. Due to the time limitation and design complexity, this project mainly focuses on the development of space-time coding on transmission for a uniform linear phased array for simplicity. For the first part, the advantages of multiple-input-multiple-output (MIMO) beamforming for radar antenna array are verified compared with other three commonly applied beamforming techniques, namely one-way beamforming, two-way beamforming, and synthetic array radar (SAR)-like beamforming. Specifically, a fair comparison among these beamforming techniques based on single transceiver, thus same physical aperture, is conducted. The resultant half-power beamwidth (HPBW) as an indicator of angular resolution is then compared to reveal better performance of MIMO beamforming. For the second part, the implementation of space-time coding, one of the signaling schemas in MIMO technology is recorded as a further implementation and exploration on MIMO beamforming. Specifically, through the studies of the spatial spectrum of the transmission rooted on the concept “colored transmission” introduced by F.L. Chevalier, the results obtained from MATLAB simulation prove that space-time coding on transmission is able to provide a wider angular coverage with less transmission pulses emitted. This is an implication that implementing space-time coding on transmission in a MIMO system improves the agility for a radar system to detect fast moving targets by spreading the transmitting energy allover the space in a single transmission.